Frequency of osteoporosis and fractures in patients with spine and spinal cord injuries - Bystrytska, Maryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
An increase in the life expectancy of patients with spine and spinal cord injuries leads to an increased risk of late complications, such as osteoporosis and fractures due to low-energy trauma. Objective: to determine the incidence of osteoporosis and fractures in individuals with spine and spinal cord injuries. Methods: 137 patients with spine and spinal cord injuries (90 men and 47 women) were examined with duration of the post-traumatic period from 3 months up to 38 years with complete transverse spinal cord injury and 137 individuals in the comparison control group. The bone mineral density was determined. Results: in patients with spine and spinal cord injuries and duration of the post-traumatic period less than 5 years, osteoporosis was detected in 40.6 % of cases, and in the comparison group normal bone mineral density was recorded (DI: 28.4–51.1; χc2 = 37.4; p < 0.0001). With an increase in the post-traumatic period for more than 5 years, osteoporosis or low bone mineral density has been revealed (in women of reproductive age and men younger than 50 years). In the comparison group, osteoporosis was not diagnosed, and a low bone mineral density was detected in 10 persons (3 men, 7 women). Among patients with spine and spinal cord injuries, the fracture rate was 18.2 % — 25 (10 men, 15 women). The average duration of the post-traumatic period at the time of the fracture was (9.7 ± 7.8) years. In the comparison group, fractures were significantly less common in 2 (1.5 %) patients (χc2 = 21.4; p < 0.0001; DI: 10.0–24.0). A significantly greater prevalence of fractures was observed in patients with spinal cord injury at the level of the lumbar spine (39.3 %) than cervical and thoracic — 11.1 % (χс2 = 5.4; p < 0.05; DI: 3.1–37.1) and 13.7 % (χс2 = 4.2; p < 0.05; DI: 0.8–34.7) respectively. The incidence of fractures increased with increasing duration of the post-traumatic period. Conclusions: the high incidence of osteoporosis and fractures in individuals with spine and spinal cord injuries causes specific preventive and curative measures to improve their bone tissue.